A rhetoric of reflection - Yancey, Kathleen Blake, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2016)
This research and practice is taking up new questions, in new sites of activity, with new theories. It includes attention to transfer of writing knowledge and practice to teaching and assessment; to portfolios; to linguistic and cultural difference; and to various media, including print and the digital.--Provided by publisher.
Contextualizing reflection / Kathleen Blake Yancey -- Reflection: the metacognitive move towards transfer of learning / Anne Beaufort -- Reiterative reflection in the 21st century writing classroom: an integrated approach to teaching for transfer / Kara Taczak and Liane Robertson -- The perils of standing alone: reflective writing in relationship to other texts / Michael Neal -- Reflecting practices: competing models of reflection in the rhetoric of prior learning assessment / Cathy Leaker and Heather Ostrum -- Reflection-action, cross-language literacy, and language dispositions / Bruce Horner -- Theorizing the reflection practices of Hmong college students: is 'reflection' a racialized discourse? / Asao Inoue And Tyler Richmond -- From selfies to self-representation in electronically mediated reflection / Elizabeth Clark -- Reflection in digital spaces: publication, conversation, collaboration / Naomi Silver -- Toward defining a social reflective pedagogy for Eportfolios / Christina McDonald -- From apprised to revised: faculty in the disciplines change what they never knew they knew / Pamela Flash -- Reflective interviewing: methodological moves for tracing tacit knowledge and challenging chronotopic representations / Kevin Roozen -- Reflecting on reflection: the writer's memo twenty-five years later / Jeff Sommers -- Reflecting and essaying: genre features, authors' practices, and implications for others / Doug Hesse -- Defining reflection: the rhetorical nature and qualities of reflection / Kathleen Blake Yancey.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Reflective learning; Reflective teaching; Transfer of training